Effects of the COVID-19 pandemic restrictions on jumping events' athletes in track and field - Bayraktar, I.; Örs, T.; Çobanoglu, H. O. (Gazi Kitabevi Tic. Ltd. Sti., 2021)
The most influential global event of the millennium is, for sure, the health problem called the Covid-19 pandemic or the coronavirus pandemic. The measures taken for this pandemic, which broke out in China at the end of 2019 and has spread rapidly all over the world, have affected all areas of social life, especially the economy. In the fight against the pandemic, it has been seen that as scientists unveil the veil of uncertainty, this disease threatens people with different health problems, especially those with obesity and related metabolic syndrome. In this sense, it is not surprising that the highest rates of illness and deaths have been in the USA. Because it is known that almost half of the adult population in the USA is obese. Sports, which play an active role in the fight against sedentary life and obesity, have been severely affected both in terms of doing sports for a healthy life and performance sports. Due to the restriction decisions taken all over the world within the scope of the fight, people have been closed to homes for a long time. The long-term health problems of the inactivity threat, which is the natural result of these decisions, is a certain reality for the people of today. Based on the findings in the fight against the pandemic, the gradual removal of the restrictions has allowed people to do regular sports again by taking measures. Gyms and fitness centers have returned to their services intermittently by taking basic measures with the "hygiene, distance, mask" triangle, and open-air sports facilities have started to be used partially within the framework of the determined rules. Major sports organizations that are postponed or canceled are the main pandemic effects regarding performance sports. It seems that the consequences of postponing Tokyo 2020 to 2021 will be discussed for a long time in terms of economic, social, political, etc. aspects. As in sport events world, continental, and national championships in athletics have been either postponed or canceled. City marathons with high participation, such as Boston, Berlin, Rome, New York City Marathon, which used to take place in a festive mood, have also been canceled due to the pandemic. Introduction In terms of training sciences, we think that our basic knowledge, especially periodization, will be updated after the Tokyo 2020 Olympic Games which have been delayed for one year. It may be possible for us to reach information about how the coaches who perform their art using the training sciences manage this process in the coming years. A change of axis seems inevitable as a result of questioning our classical knowledge and understanding of training in sports sciences due to such extraordinary situations. The pandemic period, which demonstrates that distance education with digital tools should become more widespread in the field of application of sports sciences, will highlight the coaches who are open to change and adopt modern approaches on a flexible and scientific basis. In the competitions held under the precautions, surprisingly high- performing athletes were observed. How did these performances take place despite the isolation at different levels all over the world? To what extent were the performance levels affected in countries where the pandemic was intense or not? Will these different training conditions in major competition preparation processes such as the Olympic Games result fairly? In the perspective of these and similar questions, which constitute the starting point of the study, the Top100 performances of the last 20 years (2001-2020) in the jumping event of athletics had been compared. It has been investigated whether the Covid-19 (2020) season has an effect on variables such as gender, event, continent, and how these effects are reflected on the quarters (Top25, Top50, Top75, Top100) in the Top100 performance. In the general information section, the pandemic, the coronavirus pandemic, and the different dimensions of its effects have been examined, and the IAAF Score, which is used in performance evaluation, follow-up, and comparison in athletics, have been mentioned briefly. Detailed tables and interpretations of the findings obtained by applying different statistics over 20-year Top100 performances between 2001-2020 in jumping events are given in the Results section. The striking findings of the research are also discussed in the last section. We believe that the study will shed light on scientists who are researching the pandemic effects in different events or event groups. We hope that this research will be useful in understanding the deep effects of the pandemic in the new period in which change and transformation will also take place in sports sciences.